IMF Staff papers : Volume 9 No. 1. (IMF Staff Papers; IMF Staff Papers, 1962)
The purpose of this paper is to assemble in systematic fashion the available information on the transactions of the USSR with the countries of the Soviet area and with the rest of the world during the period 1955-1958. The offset to gold and foreign exchange loans represents cash disbursements or repayments in connection with USSR credits. The entries for countries outside the Soviet area cover gold disbursements to Finland and Yugoslavia. In 1958, the Ministry of Foreign Trade of the Soviet Union published detailed statistics on the foreign trade of the USSR during the years 1955-1957. Trade among countries of the Soviet area is conducted within the framework of the over-all economic plans of the individual countries. Prices, together with quantities to be traded, are fixed in bilateral agreements, and these prices apply for the duration of the contract. Trading procedures are such that they minimize short-term capital movements. Limits are set on the indebtedness permitted in the clearing accounts, so that the indebtedness can be repaid by the end of a given year.